Comparing the effectiveness of narrative therapy and EMDR-GTEP protocols in the treatment of post-traumatic stress in children exposed to humanitarian crises - Dozio, Elisabetta; Bizouerne, Cécile; Wamba, Valdes; Atienza, Ninon (Frontiers in Child and Adolescent Psychiatry, 2024)
Background: The mental health of children living in humanitarian crisis situations is a major issue. Post-Traumatic Stress Disorder (PTSD) causes great psychological suffering and has negative consequences on children's development. The aim of the study was to analyse retrospective data collected in a mental health and psychosocial support program for children in the Central African Republic, and to compare results of two trauma-focused treatment interventions: the narrative protocol ACF/KONO, and the EMDR-based G-TEP. Both protocols are proposed in a group setting and led by para-professionals. Methods: In the program, 884 children attended a psychoeducation session and after that, 661 children (290 for ACF/KONO and 371 for G-TEP) benefited from all treatment sessions. PTSD was measured by the Children's Revised Impact of Event Scale (CRIES-8). General distress was measured by the Child Psychosocial Distress Screener (CPDS). Data were collected before and after treatment, and for 185 children were measured 5 months after the end of treatment.Results: Participants ACF/KONO shows a significant reduction on CRIES-8 (t = 44.8; p < 0.001, effect size = 2.63) and CPDS (t = 38.2; p < 0.001, effect size = 2.24). Participants to the G-TEP protocol shows a significant effect with reduced scores on the CRIES-8 (t = 49.2; p < 0.001, effect size = 2.55) and CPDS (t = 57.2; p < 0.001, effect size = 2.97). Student's t-test comparing the two groups ACF/KONO and G-TEP shows no significant difference between the two types of treatment between pre-and post-treatment for CRIES-8 scores (t = 1.744; p = 0.514, effect size = 0.040), and CPDS scores (t = 1.688; p= 0.092, effect size = 0.323). Analysis of the follow-up data for the 185 children shows that the effects of both protocols are maintained over time with mean scores at post-treatment and follow up below the clinical cut-off for both CPDS (< 8) and CRIES-8 (< 17).Conclusions: Both protocols have been shown to be effective in reducing traumatic symptoms in children exposed to conflict; they can be conducted by para-professionals and used in humanitarian crisis situations.